Managing Health Crises from an Integrated Perspective Between Nursing and Health Administration - Aldousari, Nourah Yousef Mohammed; Ghonaim, Hadeel Mohammed; Alshreef, Zainah Balqasiem Ali; Sulong, Aisha Abdulrahman; Almwalad, Bashair Jameel; Albishi, Nouf Mubarek Abdullah; Aighamdi, Saeed Mohammed Bin Mesfer; Alharbi, Khaled Abdullah; Alghamdi, Jamla Nawar Mohammed; Khalil, Najat Abduallh (Journal of Posthumanism, 2024)
Background: The rise of global health crises reveals vulnerabilities in isolated healthcare leadership. The COVID-19 pandemic illustrated the dangers of disconnect between administrative strategy and clinical nursing, compromising patient safety and operational continuity. Objective: This paper posits that effective health crisis management relies on a collaborative relationship between nursing and health administration. Methods: Through a comprehensive review of empirical studies and frameworks such as HICS and CERC, it investigates the interdependent roles of nursing and administration, exploring collaboration models like dyad leadership and shared governance. Findings: Integrated systems show greater adaptability and resilience, necessitating interdisciplinary staffing, shared decision-making, bi-directional communication, and joint simulation training for effective crisis management. Conclusion: To ensure patient safety and system survival amidst global health challenges, integrating nursing and health administration is both an ethical and operational necessity, advocating for the dismantling of traditional silos to create a unified leadership model